2014
DOI: 10.1007/s10157-014-0942-9
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a risk score for contrast-induced nephropathy after cardiac catheterization in Chinese patients

Abstract: A simple risk score for prediction of CIN development after cardiac catheterization in Chinese patients was built up by this study. Use of this risk score may help clinicians to perform early preventative strategies to minimize the risk of CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
42
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 26 publications
10
42
2
Order By: Relevance
“…History of HTN (p value=0.542), which was consistent with Gao et al, [14], who demonstrated that history of hypertension was significant predictor of CIN (p value=0.001)…”
supporting
confidence: 88%
See 4 more Smart Citations
“…History of HTN (p value=0.542), which was consistent with Gao et al, [14], who demonstrated that history of hypertension was significant predictor of CIN (p value=0.001)…”
supporting
confidence: 88%
“…Contrast volume used ≥ 200 ml (p value=0.048), which was consistent with Gao et al, [14], who retrospectively studied 3945 Asian patients undergoing coronary angiography or PCI and demonstrated that the contrast volume used >200 mL was associated with a significantly higher risk of CIN and the CIN risk would be increased with the increment of contrast volume.…”
supporting
confidence: 85%
See 3 more Smart Citations